Differentiation of Population Incomes and the Role of Antimonopoly Regulation in Reducing the Threat of Economic Security - K. A. Kudryavtsev (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article discusses the differentiation of incomes of the population as a threat to economic security and determines the possibility of using anti-monopoly regulation tools to reduce household monetary expenditures in order to level income inequality. The study analyzes the level of income inequality in the world and in Russia. On the basis of statistical data, a new indicator is being introduced for assessing the state of the economic security of the Russian Federation - the rate of return on households and a trend is being calculated for it. According to the results of the study of the transformation of antitrust regulation during the adoption of the third and fourth "antimonopoly packages", it was revealed that in order to open up the development of entrepreneurship in the country, the state had to sacrifice some of their legitimate interests and the interests of citizens. However, the implementation of a set of measures aimed at liberalizing the regulation of the protection of competition did not lead to a decrease in income differentiation and a significant increase in consumer savings, which is confirmed by the dynamics of the coefficient of funds and the rate of return on households. In order for these ratios to have a positive trend, consideration should be given to reducing the cash costs of households. In this regard, the author has developed a number of measures to improve anti-monopoly regulation.